Adaptação da escala UPPS-P e sua aplicabilidade na população brasileira - Marina Saraiva Garcia (2018)
Impulsivity is a complex and according to the model of impulsive behavior UPPS construct would consist of five factors: a) urgency (tendency to act rashly hhen faced to intense negative emotions), b) lack of premeditation (inability to consider the potenctial consequences of ones behavior), c) lack of perseverance (lack of ability to stay focused on a task that may be boring or difficult), d) sensation seeking (composed by need of excitement and stimulations, as well as openness to new experiences), e) positive urgency (tendecy to rash action in response to very positive mood). Objective: The aim of this study is adaptation of positive urgency of UPPS-P to Brazilian population. After that, the goal was to analyze factorial structure of Brazilian version and get norms to interpret the scores of UPPS-P in brazilian adults. Method: To achieve the first objective, the original itens of positive urgency of English version of the UPPS-P was translated into Portuguese by two bilingual researchers. After this, the scale was unified e reviewed by researches of differents regions of Brazil. After the sugestions of experts, the itens were translated to the English by a native American who is both fluent in Portuguese and in English. The authors of the scale compared the original version with the one witch was translated to the English and there were changes to keep the semantic equivalence. Those itens were joined to the brazilian version of UPPS and, in the second fase of the research, were applied on an adult sample invited by social networks, universities and associations. The current study had 724 participants among 18 and 60 years old. Results: The fatorial analysis for the data is proper. In the confirmatory fatorial analysis with an obliq model, the values were considered proper. All scores of the scale showed negative and significative correlations with age. About genre, it was found significative difference in the fator sensation seeking. Individuals with higher educational level showed minors scores in all the factors. It was not found diferences among groups in the region variable. Conclusion: The current study presents the cross-cultural adaptation of UPPS-P for brazilian population.